MODELING AND SOFTWARE IMPLEMENTATION OF 3D VISUALIZATION (AT EXAMPLE OF DEVELOPMENT OF INTERIOR) (Modern information system and technologies, 2018)
In the article the methods of modeling of 3D objects are considered. The purpose of the work is to develop mathematical models of real architectural objects and simulate the 3D scene. Development methods include studying the theory of simulation using splines and R-functions, using the modern software environment of the Audodesk 3ds Max.